‘Smart’ in Between People and the City - Ramona Hosu; Ioan Hosu (Transylvanian Review of Administrative Sciences, 2019)
The present paper intends to identify the current meanings of ‘smart’ in the concepts ‘smart cities’ and ‘smart people’ by debating on place identity conjoined with individual and community identity, as currently discussed in specialized literature, in some media outlets and in some official documents of specialized institutions. The study debates on the dichotomy ‘technology and/or the human factor’ starting from a general discussion on technological determinism vs. the role of the social context, on possible new identities associated with the contemporary digimodernist society, and it ends with a discussion on the role of human-centered approaches in innovation processes that contribute to the construction of smart cities, which is the case of Cluj-Napoca, Romania.